2015
DOI: 10.1007/s00384-015-2392-6
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid hyperplasia of the colon and its association with underlying allergic airway diseases

Abstract: Our results indicate that lymphoid hyperplasia in the large intestine may be associated with allergic airway diseases rather than with food allergies; thus, its presence may be useful to detect patients with underlying airway hyperreactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A few studies have suggested that there is a relationship between asthma and lymphoid hyperplasia of nonrespiratory organs including the gastrointestinal tract. [18,19] For instance, as many as 85.7% of patients with lymphoid hyperplasia of the large intestine (cecum, colon, and rectum) have allergic airway diseases and positive reactions to inhalant allergens. [18,19] Because the appendix is an organ with a large number of lymphoid follicles, asthma-induced reactive lymphoid hyperplasia could manifest in the lumen of appendix to cause obstruction or inflammation in appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested that there is a relationship between asthma and lymphoid hyperplasia of nonrespiratory organs including the gastrointestinal tract. [18,19] For instance, as many as 85.7% of patients with lymphoid hyperplasia of the large intestine (cecum, colon, and rectum) have allergic airway diseases and positive reactions to inhalant allergens. [18,19] Because the appendix is an organ with a large number of lymphoid follicles, asthma-induced reactive lymphoid hyperplasia could manifest in the lumen of appendix to cause obstruction or inflammation in appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…LH occurs in the rapidly increasing lymphocytic cells. It has a spherical shape with color of light yellow or light gray [11]. LH can be related to several diseases such as immunodeficiency, HIV/AIDS, selective IgA deficiency, and Helicobacter pylori infections [12].…”
Section: Introductionmentioning
confidence: 99%